A philosophical analysis of sacrifice as a means to an end in contemporary Nigerian Christianity and Yoruba traditional religion (2018)
History reveals Io us the significant position occupied by sacrifice in most world religions. Today, in spite of the enormous pressure of Western civilization or what we call modernity, people still offer sacrifices in different religions. Sacrifice in the context of this paper involves a cost, depriving oneself of what is valuable and sometimes precious. There are several factors necessitating the offering of sacrifice, one of which is sacrifice serving as a “means” to an “end.” What is this “means” and what is this “end?" Why do people offer sacrifices? Is it because of the love for the deity or is their sacrifice premised on their own needs? What is the actual goal of a sacrifice? What is the real reason why people give sacrificially? Is a sacrifice attached to a need or what the one offering the sacrifice Stands to benefit? This paper attempts to answer these vital questions attached to sacrifice in the contexts of Christianity and Yoruba Traditional Religion. It is a philosophical analysis of a fundamental purpose of sacrifice- a “means" to an “end" in the two selected religions. The paper adopts E. B. Taylor ’s theory which sees Sacrifice as a means of “bribing" the gods or of paying homage to them. The methods of data Collection includes consultation of relevant books and journals on the subject of discussion.